Isoflavone and protein content in soybeans grains submitted to flooding at different stages of development Teor de isoflavonas e proteínas nos grãos de soja submetida ao alagamento em diferentes estádios de desenvolvimento - Camila Argenta Fante (Ciência Rural, 2011)
The stress imposed on plants by soil flooding constitutes a major barrier to growth and productivity. The identification of soybean varieties that produce higher levels of isoflavones, is necessary as soybeans have been used as human food to reduce risks of chronic diseases. Thus, this study was conducted with the objective of quantifying proteins and isoflavones in soybean cultivars subjected to flooding at various stages of development. The cultivars 'BRS267', 'BRS257' and 'BRS213' were subjected to 15 days of flooding, starting at the stages V6 and V8 and 11 days under stress starting at the stage R4. The proteins in the grain were extracted and quantified and analyzed by SDS-PAGE electrophoresis. Isoflavones were extracted, separated and quantified on HPLC. The electrophoretic analysis of the three cultivars under study revealed the same pattern of banding relative to the total protein regardless of the treatment. However, it was noted that flooding led to an increase in the total contents of isoflavones in the BRS 267 plants flooded in stage R4, remaining constant in other cultivars. O estresse imposto às plantas pelo alagamento do solo constitui uma barreira para o crescimento e produtividade destas. A identificação de cultivares de soja que possam produzir maior teor de isoflavonas torna-se necessária à medida que a soja vem sendo utilizada na alimentação humana e para redução dos riscos de doenças crônicas. Dessa forma, o presente estudo foi realizado com o objetivo de quantificar isoflavonas e proteínas em cultivares de soja submetidas ao alagamento em diferentes estádios de desenvolvimento. As cultivares 'BRS 267', 'BRS 257' e 'BRS 213' foram submetidas a 15 dias de alagamento, nos estádios V6 e V8 e 11 dias sob estresse, no estádio R4. As proteínas no grão foram extraídas e quantificadas e analisadas as eletroforeses em SDS-PAGE. Os isoflavonóides foram extraídos, separados e quantificados por HPLC. A análise por eletroforese das três cultivares revelou o mesmo padrão de bandas relativas às proteínas totais, independente do tratamento utilizado. O alagamento promoveu aumento no teor total de isoflavonas nas plantas alagadas no estádio R4 da cultivar 'BRS 267', permanecendo constante nas demais cultivares.